2014
DOI: 10.2337/dc13-2603
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of C-Peptide and Its Determinants in North American Children at Risk for Type 1 Diabetes

Abstract: OBJECTIVETo determine basal and stimulated C-peptide percentiles in North American children and adolescents at risk for type 1 diabetes (T1D) and to examine factors associated with this distribution in the Diabetes Prevention Trial–Type 1 (DPT-1).RESEARCH DESIGN AND METHODSWe included 582 subjects aged 4–18 years at randomization in the DPT-1 trials. A 2-h oral glucose tolerance test (OGTT) was performed at baseline and every 6 months during the 5-year follow-up period. The percentile values of C-peptide after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Both glucose and C‐peptide measures have proved useful in predicting T1D onset in autoantibody positive individuals, 9–11 highlighting the importance of associations between mod + vig PA and fasting glucose, 120‐min glucose, glucose AUC, and fasting C‐peptide, 120‐min C‐peptide, and C‐peptide AUC as reported herein. We also confirmed the association of both child age and BMIz score to C‐peptide results, supporting prior work suggesting that any effort to identify C‐peptide cut‐points to classify individuals as having loss of beta‐cell function must take these factors into account 35 …”
Section: Discussionsupporting
confidence: 86%
“…Both glucose and C‐peptide measures have proved useful in predicting T1D onset in autoantibody positive individuals, 9–11 highlighting the importance of associations between mod + vig PA and fasting glucose, 120‐min glucose, glucose AUC, and fasting C‐peptide, 120‐min C‐peptide, and C‐peptide AUC as reported herein. We also confirmed the association of both child age and BMIz score to C‐peptide results, supporting prior work suggesting that any effort to identify C‐peptide cut‐points to classify individuals as having loss of beta‐cell function must take these factors into account 35 …”
Section: Discussionsupporting
confidence: 86%
“…However, the coefficient estimates derived from the Cox proportional hazards model may be biased as a result of violating assumptions of independence. In the previous studies (20,21) that examined the relationship between metabolic and immunologic risk factors among at-risk subjects, the results showed the significant correlations among some of the risk factors. As well, in previous studies (2225) some autoantibodies have been shown to be age related.…”
Section: Discussionmentioning
confidence: 87%
“…Also, age continues to affect C-peptide levels up to 4 years from diagnosis [35]. It has also been shown that sex is significantly associated only with stimulated C-peptide [27]. Inclusion of age and sex did not improve the model (M6 vs M8) [36].…”
Section: Modelling Residual Beta Cell Functionmentioning
confidence: 95%
“…Thus, apparently the other clinical measures accounted for the effect of age and sex on beta cell function. It is still to be tested how well the model works in the range of very low C-peptide levels that still respond to hyperglycaemia with increased C-peptide production [40] and if it performs equally well over the full spectrum of Cpeptide values [27].…”
Section: Modelling Residual Beta Cell Functionmentioning
confidence: 99%
See 1 more Smart Citation